Design of Maritime French Tourism Teaching Material for Riau Islands Students - Indrayatti Wahyu; Zulaeha Ida; Yuniawan Tommi; Vivi Widayanti Diah (SHS Web of Conferences)
Maritime tourism is one of the Riau Islands' natural resource potentials. French Tourism is an additional foreign language skill for English Department students at Universitas Maritim Raja Ali Haji, Tanjungpinang, Riau Islands. Teaching materials have an essential role in teaching French-specific purposes. The purpose of this study is to design Maritime French Tourism teaching materials using the literature review method. The design of teaching materials refers to previous studies on developing teaching materials for tour guides to determine the language competencies and content that students need to improve their skills as future tour guides in the Riau Islands. Speaking skill is should be the most practiced language skills in tourism French courses. The teaching materials should include specific materials about tour guide professionalism and French language training material that comprises the Riau Islands' maritime tourism context and encouraging communicative competence.